REseau MOllusques des Rendements Aquacoles huitre creuse (REMORA) - Fleury, Pierre-gildas; Ruelle, Francois; Claude, Serge; Palvadeau, Hubert; Robert, Stephane; Vercelli, Catherine; Chabirand, Jean-michel; D'Amico, Florence (1999)
The monitoring network IFREMER /REMORA is assessing on a yearly basis, from February to December, mortality, growth and quality criteria of two oyster batches ("juveniles" = one-year class and "adults" = two-years class), deployed among various stations of the main French oyster areas. This network is a tool for trend estimations (geographic and chronological, on the national scale) it must not be considered as an accurate estimation of professional oyster ongrowings. Based on REMORA results, generally tallied with professional observations, 1998 on the whole was a second year of low mortality. However several areas remained affected by significant mortalities : the baie des Veys (in Normandy), Morlaix and Pen-Bé (in Brittany) and Marennes (in Charente-Maritime). The year 1998 was overall a very poor year for growth : the mean oyster weight reached 60.9 grammes. This lack of growth was also recorded in the quality indexes (fresh and dry meat weight) which were clearly below the average values. Another problem of quality is the steady increase, from year to year, of the infestation of oysters by the Annelid worm Polydora, which was particularly important in 1998 in the Arcachon bay. Le réseau IFREMER /REMORA suit chaque année, de février à décembre, la mortalité, la croissance et des critères de qualité de 2 lots d'huîtres ("juvéniles" = 1 an et "adultes" = 2 ans) qui sont répartis entre différentes stations dans les principaux secteurs ostréicoles français. Ce réseau est un outil d'évaluation des tendances (géographiques et chronologiques, globales à l'échelle nationale) il ne doit pas être perçu comme un estimateur précis des croissances obtenues chez les producteurs. Au vu des résultats du réseau, en général corroborés chez les professionnels, 1998 confirme, dans l'ensemble, la régression des phénomènes de mortalité des animaux, régreesion déjà observée en 1997. Des secteurs restent néanmoins le lieu de fortes mortalités : la baie des Veys (en Normandie), Pen-Bé (en Bretagne) et Marennes (en ...